2020
DOI: 10.14309/ajg.0000000000000732
|View full text |Cite
|
Sign up to set email alerts
|

Lipase Elevation in Patients With COVID-19

Abstract: INTRODUCTION: Although coronavirus disease (COVID-19) has been associated with gastrointestinal manifestations, its effect on the pancreas remains unclear. We aimed to assess the frequency and characteristics of hyperlipasemia in patients with COVID-19. METHODS: A retrospective cohort study of hospitalized patients across 6 US centers with COVID-19. RESULTS: Of 71 patients, 9 (12.1%) developed hyperlipasemia, with 2 (2.8%) greater than 3 times upper limit of normal. No patient developed acute pancreatitis. Hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
115
5
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(142 citation statements)
references
References 5 publications
3
115
5
10
Order By: Relevance
“…A cute pancreatitis is one of the most common conditions leading to emergency hospital admission. 1 Its variable etiologies include vascular events, 2 drugs, 3 and genetic factors, 4 but the ultimate clinical manifestation is fairly uniform. 5 It involves edema of the gland, the development of pancreatic and extrapancreatic necrosis and systemic complications leading to (multi)organ failure.…”
Section: Cell Signaling Of Pancreatic Duct Pressure and Its Role In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…A cute pancreatitis is one of the most common conditions leading to emergency hospital admission. 1 Its variable etiologies include vascular events, 2 drugs, 3 and genetic factors, 4 but the ultimate clinical manifestation is fairly uniform. 5 It involves edema of the gland, the development of pancreatic and extrapancreatic necrosis and systemic complications leading to (multi)organ failure.…”
Section: Cell Signaling Of Pancreatic Duct Pressure and Its Role In Tmentioning
confidence: 99%
“…3 An increasing number of publications have reported that SARS-CoV-2 targets the pancreas resulting in elevation of serum lipase activity or rarely even frank pancreatitis. [4][5][6][7] Autopsy data suggest that the incidence of focal pancreatitis in COVID-19 may be higher than diagnosed clinically. 8 However, it is conceivable that the virus targets not only the pancreas, but also adipocytes causing increased lipolysis through the adipose triglyceride lipase (Figure 1, A).…”
mentioning
confidence: 99%
“…However, direct connection of acute pancreatitis with ritonavia-induced hypertriglyceridemia was only illustrated in few cases [7]. Meanwhile, COVID-19 patients with hypertriglyceridemia was not seen clinical acute pancreatitis and in this case, hypertriglyceridemia occurred after incidence of acute pancreatitis [8].…”
Section: Discussionmentioning
confidence: 75%
“…Thirdly, elevation of pancreatic enzymes without clinical evidence of pancreatitis has also been reported in literature in patients of COVID 19 infection. A retrospective cohort study by McNabb-Baltar et al [3] in 71 patients hospitalized for COVID-19 found that, only 9 (12.1%) had hyperlipasemia (defined in this study as an elevated lipase level above the upper limit of normal (>60 U/ L)), with two cases (2.8%) having greater than 3 fold elevation but without imaging evidence of acute pancreatitis. Two additional patients with hyperlipasemia (62 U/L and 136 U/L) who underwent abdominal CT imaging had mild fat stranding around the pancreas and gallbladder (but did not meet radiologic criteria for pancreatitis) and a normal examination, respectively.…”
mentioning
confidence: 59%